Ubiquitin-dependent proteolysis in yeast cells expressing neurotoxic proteins - Braun, Ralf J. (Frontiers in Molecular Neuroscience, 2015)
Critically impaired protein degradation is discussed to contribute to neurodegenerative disorders, including Parkinson’s, Huntington’s, Alzheimer’s, and motor neuron diseases. Misfolded, aggregated, or surplus proteins are efficiently degraded via distinct protein degradation pathways, including the ubiquitin-proteasome system, autophagy, and vesicular trafficking. These pathways are regulated by covalent modification of target proteins with the small protein ubiquitin and are evolutionary highly conserved from humans to yeast. The yeast Saccharomyces cerevisiae is an established model for deciphering mechanisms of protein degradation, and for the elucidation of pathways underlying programmed cell death. The expression of human neurotoxic proteins triggers cell death in yeast, with neurotoxic protein-specific differences. Therefore, yeast cell death models are suitable for analyzing the role of protein degradation pathways in modulating cell death upon expression of disease-causing proteins. This review summarizes which protein degradation pathways are affected in these yeast models, and how they are involved in the execution of cell death. I will discuss to which extent this mimics the situation in other neurotoxic models, and how this may contribute to a better understanding of human disorders.